Immobilisation of arsenic, copper, manganese and lead in gold mine tailings by oil palm empty fruit bunch and rice husk biochars - Claoston anak Nardon (2015)
Biochar has recently received great attention due to its physico-chemical properties which affects soil fertility and contaminant immobilisation as well as serving carbon sinks and sequestration in the soil system. In this project, biochars were produced from empty fruit bunch (EFB) and rice husk (RH) by slow pyrolysis at different temperatures (350, 500 and 650 oC) and the physico-chemical properties of each biochar were analysed. The results show that the porosity (BET surface area), ash content, EC and pH value of EFB and RH biochars increased with increasing pyrolysis temperature. However the amount of biochar produced, its CEC and N, C and S content decreased with increased in temperature. The FTIR spectra were similar for RH biochars but the functional groups were more distinct in the EFB biochars spectra. There were significant reductions in functional groups as pyrolysis temperature increased, especially for the EFB biochar. However, the total acidity of the functional groups increased with pyrolysis temperature for both biochars. The first experiment that has been conducted was on adsorption studies. These studies have been done to oversee the potential of EFB and RH biochars in adsorbing As, Mn, Cu and Pb from aqueous solution of different concentrations. In this research, adsorption of As, Mn, Cu and Pb increased with increasing initial concentrations. This is due to the higher concentration gradient to overcome the mass transfer energy. The experiment also showed that adsorption of As, Mn, Cu and Pb by EFB and RH biochars fitted well to the Langmuir isotherm. The RL values also was found between 0 and 1, and showed that the adsorption of As, Mn,Cu and Pb were a favourable process. Furthermore, to investigate the effect of biochar application in the retention of heavy metals in gold mine tailings, the tailings were incubated with different rates of RH and EFB biochars for 2, 8 and 24 weeks. The application of biochar significantly reduced the concentrations of extractable Pb, Mn and Cu in the tailings. However, the opposite was observed for As. The addition of biochar also increased the pH of the tailings throughout the incubation periods. The EFB and RH biochars produced at 650 oC were better in reducing the extractable Cu, Pb and Mn. However, EFB650 and RH650 biochars were also the worst in reducing the extractable As in the tailings. Besides, a leaching experiment was conducted by mixing the tailings with EFB and RH biochars at different rates (0, 5, 15 and 20% (w/w)) and leached with simulated rain water (SRW) every 15 days for 2 months. The results showed that with increasing rates of both biochars, the concentrations of As, Pb, Cu and Mn in the leachates were significantly higher than the control. These experiments (adsorption, incubation and leaching studies) in aqueous solutions and tailings amended with EFB and RH biochars that were produced at 350, 500 and 650 oC showed that the capability of these biochars in reducing the available As, Cu, Mn and Pb were dependent on many aspects such as BET surface area, porosity and variety of functional groups in the biochars as well as several sorption processes,which includes adsorption to mineral (tailings) surfaces, formation of stable complexes with organic ligands, ion exchange and surface precipitation. Overall,the evidences raised by the current study proved that application of biochars as an amendment in polluted area, such as mine tailings, can adsorb or immobilized heavy metals and other pollutants, hence reducing the availability of pollutants in particular polluted area. Thus, utilization of biochar will create a cleaner environment.